CMOS low voltage class D amplifier - Khin Thida Aung. (2008)
This dissertation describes the theoretical and practical work on the analysis, design and implementation of a closed loop low power low voltage pulse width modulation (PWM) Class D amplifier. The objective of using the closed loop Class D amplifier is to improve the THD reduction, gain linearity, and to reduce output dc bias current. A Class D amplifier with feedback is proposed in this dissertation and the Total Harmonic Distortion (THD) of the feedback is described.